3D interactive courseware for medical education cardiac anatomy : myocardial infarction - Rathi Thevy, Jevanantham (2014)
3D Interactive courseware for Medical education (Cardiac Anatomy: myocardial Infarction) is an educational courseware that will provide information about myocardial infarction, how it occurs and the complication that might cause to the organ and health tips to prevent cardiac related diseases in an interactive way. This could help the user to gain knowledge on cardiac related topics and help them to seek preventions. The aim of this courseware is to provide information on coronary heart disease through high quality three dimensional models and allow users to interact to obtain information included into this educational courseware. The objectives of this project to educate users on myocardial infarction with a details 3D models, is possible when 3D interactive courseware can utilized for lessons, to implement the use of 3D interactive courseware widely to make the knowledge reach everyone. This could create medical awareness among Malaysian regarding health issues since it's been developed as an interactive 3D courseware that provides the concepts appropriately for cardiac anatomy learners. The scope of the project are medical students, lecturers, pre-medical students, nursing students, patients or anyone who is looking for a basic Anatomy review to learn about anatomical details on their computers. The courseware could provide an accurate look at the anatomy of the most important organ in human body, Heart and specifically artery where the heart attack occurs. 3D Interactive courseware for Medical education would be an outstanding experience of learning for users. Quiz included in the courseware could be attempted by users to evaluate their understanding on coronary heart disease.